Mutation Profiling Indicates High Grade Prostatic Intraepithelial Neoplasia as Distant Precursors of Adjacent Invasive Prostatic Adenocarcinoma - Gerrin, Sean J. (Prostate, 2016)
INTRODUCTION: High Grade Prostatic Intraepithelial Neoplasia (HGPIN) is the putative precursor lesion to prostatic adenocarcinoma (PCa), but the precise relationship between HGPIN and PCa remains unclear. METHODS: We performed a molecular case study in which we studied mutation profiles of six tumor-associated HGPIN lesions in a single case of TMPRSS2:ERG fusion positive Gleason score 7 PCa that we had previously mapped for somatic mutations in adjacent Gleason pattern 3 and 4 foci, using microdissection and targeted deep-sequencing. RESULTS: A total of 32 tumor-specific mutated sites were successfully amplified and sequenced, including 25 truncal mutations and 7 mutations that were specific to either the Gp3 or Gp4 foci. All six HGPIN foci shared the same tumor-specific TMPRSS2:ERG fusion breakpoint, establishing that they were all clonally related to the adjacent invasive tumor. Among the 32 gene targets mutated in the invasive tumor, only mutation of the OR2AP1 gene, a truncal mutation, was found in a single focus of HGPIN. The remaining gene targets that were successfully sequenced were wild-type in all other HGPIN foci. DISCUSSION: This study demonstrates the feasibility of targeted mutation profiling of HGPIN lesions, which will be important to understand PCa tumorigenesis. The results in this case, showing a remarkable absence of truncal mutations in HGPIN lesions bearing the tumor-specific ERG fusion, indicate HGPIN lesions may be relatively stable genetically and argue against a stepwise clonal evolution model of HGPIN to PCa.